GE_GERICHTE P/19704/2016 vom 15. Oktober 2018 - GE Cour de justice (2018)
PRINCIPE DE L'ACCUSATION; DROIT DES ÉTRANGERS; EMPLOI(TRAVAIL); AUTORISATION DE SÉJOUR; EMPLOYEUR ; ORGANE DE FAIT | CPP.9; CPP.325; CPP.10.al2; LEtr.116.al1.letb; LEtr.117.al1; LEtr.91